Differential regulation of primary carbides in high carbon bearing steel using pulsed current to improve corrosion resistance - Mingkui Zhang; Le Ren; Xiaoshan Huang; Mengcheng Zhou; Jinchao Ma; Tao Zhang; Jide Liu; Jingdong Guo; Xinfang Zhang (Journal of Materials Research and Technology)
In high-carbon alloy steels, the difference in properties between the primary carbides and the matrix leads to stress concentration and electrochemical corrosion during use, which leads to corrosion, cracking, wear, peeling, and ultimately material failure. In the traditional homogenization annealing methods, M2C carbides are slowly eliminated, while MC carbides are significantly coarsened. Based on the difference in electrical properties between the primary carbides and the matrix, this study innovatively uses pulsed electric current to effectively eliminate M2C carbides at low temperatures, while slowing down the coarsening of MC carbides. With the primary carbides diminished, electrochemical testing indicates that the corrosion potential of the sample is increased by 26.33% after 1 h pulsed electric current treatment at 1100 °C, demonstrating excellent corrosion resistance. The new method of regulating primary carbides proposed in this study can provide a new way to study the change of corrosion resistance during the microstructural evolution.